2017
DOI: 10.1111/jgh.13512
|View full text |Cite
|
Sign up to set email alerts
|

Telbivudine therapy for chronic hepatitis B: A journey to identify super‐responders and to optimize treatment using the roadmap model

Abstract: Hepatitis B virus (HBV) infection is one of the most serious health problems worldwide with a high risk for cirrhosis and liver cancer. Several antiviral agents have been approved for the treatment of chronic hepatitis B, leading to a rapid reduction in HBV DNA and normalization of serum alanine aminotransferase levels. Telbivudine, a potent inhibitor of HBV replication, has been shown to be well tolerated. Because of the emergence of drug resistance, optimization strategies for telbivudine therapy have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…[13] Mild ALT levels and low HBV DNA levels (eg <20,000 IU / mL for HBeAg-positive and <2,000 IU / mL for HBeAg-negative patients) can be predictors of the long-term benefit and safety profile of anti-HBV therapy. [14] In this study, the results of multiple logistic regression analysis showed a significant difference between the administration of Telbivudine as a hepatitis B treatment with lower serum HBV DNA levels compared to the administration of Tenofovir at the 12-month follow-up therapy.…”
Section: Discussion Smentioning
confidence: 56%
“…[13] Mild ALT levels and low HBV DNA levels (eg <20,000 IU / mL for HBeAg-positive and <2,000 IU / mL for HBeAg-negative patients) can be predictors of the long-term benefit and safety profile of anti-HBV therapy. [14] In this study, the results of multiple logistic regression analysis showed a significant difference between the administration of Telbivudine as a hepatitis B treatment with lower serum HBV DNA levels compared to the administration of Tenofovir at the 12-month follow-up therapy.…”
Section: Discussion Smentioning
confidence: 56%
“…According to international guidelines and the roadmap concept, both the addition of a nucleotide analogue or simply switching to a more potent drug are suggested for chronic hepatitis B (CHB) patients receiving telbivudine (LdT) therapy who exhibit drug resistance or an insufficient response [1][2][3][4][5]. Switching to tenofovir disoproxil fumarate (TDF) is also regarded as the appropriate rescue therapy for patients with LdT-related myopathy or neuropathy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus infection causes chronic hepatitis and complications that can pose serious hazards to human health worldwide [1,2]. As reported by the World Health Organization, approximately 2 billion people have been infected with the hepatitis B virus [3], with over 400 million people developing chronic hepatitis [4,5].…”
Section: Introductionmentioning
confidence: 99%